The Various Designs of Storage Solar Collectors: A Review - Omer K Ahmed; Sameer Algburi; Raid W. Daouda; Hawazen N Shubat; Enas F Aziz (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The use of solar energy to heat water is the more critical application of solar energy. Researchers are trying to develop different methods to improve the efficiency of solar water heaters to meet the increasing demand for hot water due to global population growth. To reduce the cost and increase the efficiency of solar heaters, the solar collector and the storage tank are combined into one part, and this system is called solar storage collector. It can be defined as geometric shapes filled with water, painted black, and placed under the influence of sunlight to gain the largest amount of solar energy. This article presents the various designs of solar storage collector. This review showed that design variables and design shape significantly affect the efficiency of the solar heating system. Climate and operational factors also have a strong influence on the performance of solar heating. Furthermore, scientists and researchers have also used nanotechnology, solar cells, and mirrors to improve other stored solar collectors' performance. Finally, recently published articles indicate an increase in interest in improving the efficiency of solar storage collector by creating new designs that enhance the economic and practical viability.